Comparison of the Effects of Oral Nizatidine versus Famotidine on Intragastric pH and Gastric Emptying in a Stress Rat Model - Dong Han Yeom; Hyun Seok Choi; Min Seob Kim; Myeong Hwan Yu; Jisong You; Moon Young Lee; Yong Sung Kim (Yong Chan Lee, 2022)
Background/Aims Histamine-2 receptor antagonists (H2RA) are used to treat acid-related disorders and functional dyspepsia. In contrast to other H2RAs, nizatidine promotes gastric emptying (GE). We investigated the effects of nizatidine and famotidine on intragastric pH and the GE rate in rats exposed to stress. Materials and Methods We used 8-week-old male Wistar rats. Based on administration of water or drugs after an overnight fast, the animals were categorized into the nonstress-water, stress-water, stress-nizatidine, stress-famotidine, and stress-nizatidine with mosapride groups. The rats had access to pre-weighed food for 10 minutes, and those in the stress groups were exposed to 1 hour of restraint stress. Intragastric pH was measured under isoflurane anesthesia, and the GE rate was measured after the rats were sacrificed. Results The GE rate was significantly lower in the stress-water and stress-famotidine groups than in the nonstress-water group. However, GE in the stress-nizatidine and stress-nizatidine with mosapride group did not significantly differ from that in the nonstress- water group. The GE rate was significantly higher in the stress-nizatidine with mosapride than in the stress-famotidine group. Intragastric pH was significantly higher in the stress-nizatidine and stress-famotidine groups than in the stress-water group. Nonetheless, there was no significant difference in pH between the stress-nizatidine and stress-famotidine groups. The intragastric pH was slightly but significantly higher in the stress-nizatidine with mosapride group than in the stress-nizatidine and stress-famotidine groups. Conclusions In contrast to famotidine, nizatidine prevents stress-induced GE delay, which suggests that nizatidine is superior to other H2RAs for treatment of functional dyspepsia associated with delayed GE.